Visibility without Recognition: Assessing the Effectiveness and Structural Limits of Catalonia's Paradiplomacy in Pursuit of Self-Determination - Kafiil, Gibran Muhammad; Nyi Ayu Keisha Alya (Journal of Paradiplomacy and City Networks, 2026)
This study explores why paradiplomacy has emerged as a central yet contested instrument in Catalonia’s ongoing quest for self-secession from Spain. Through a multidisciplinary approach, the research applies Stéphane Paquin’s theory of paradiplomacy, Pinos and Sacramento’s counter-paradiplomacy framework, and the normative principles of self-determination theory to critically assess the strategic deployment of subnational diplomacy by Catalonia. Drawing on a synthesis of peer-reviewed literature published since 2016, the study investigates how Catalonia has utilized various paradiplomatic mechanisms, including identity diplomacy, targeted public diplomacy campaigns, and active participation in transnational and European networks, to reframe its independence movement and seek symbolic legitimacy in the international arena. These efforts aim to bypass Spain’s exclusive control over foreign policy and cultivate external support for the Catalan cause. However, the research also analyzes Spain’s robust countermeasures, including legal and constitutional suppression, strategic narrative framing, and institutional constraints within international organizations, which collectively work to contain and delegitimize Catalonia’s external outreach. While the findings indicate that Catalonia has been moderately successful in building soft power and gaining symbolic recognition, the study concludes that paradiplomacy alone remains structurally inadequate to achieve formal recognition of self-secession, particularly within the constraints of international law and the liberal-democratic order.